Fiscal sustainability and policy implications for the euro area - Fabrizio Balassone; Jorge Correia da Cunha; Geert Langenus; Bernhard Manzke; Jeanne Pavot; Doris Prammer; Pietro Tommasino (Deutsche Bundesbank, 2009)
In this paper we examine the sustainability of euro area public finances against the backdrop of population ageing. We critically assess the widely used projections of the Working Group on Ageing Populations (AWG) of the EU's Economic Policy Committee and argue that ageing costs may be higher than projected in the AWG reference scenario. Taking into account adjusted headline estimates for ageing costs, largely based upon the sensitivity analysis carried out by the AWG, we consider alternative indicators to quantify sustainability gaps for euro area countries. With respect to the policy implications, we assess the appropriateness of different budgetary strategies to restore fiscal sustainability taking into account intergenerational equity. Our stylised analysis based upon the lifetime contribution to the government's primary balance of different generations suggests that an important degree of pre-funding of the ageing costs is necessary to avoid shifting the burden of adjustment in a disproportionate way to future generations. For many euro area countries this implies that the medium-term targets defined in the context of the revised stability and growth pact would ideally need to be revised upwards to significant surpluses.
Keywords: H55; H60; 330; population ageing; fiscal sustainability; generational accounting; medium-term objectives for fiscal policy; Alternde Bevölkerung; Öffentliche Ausgaben; Intergenerative Belastungsrechnung; Finanzpolitik; Nachhaltigkeit; EU-Staaten